Metaphor and Cultural Cognition: A Systematic Review - Shafiei, Fatemeh (LANGUAGE ART, 2025)
Over the past decades, the discussion of cultural cognition and the relationship between conceptual metaphors in cognitive linguistics has captured the attention of scholars and researchers across various fields of cognitive linguistics and cognitive social sciences. Cultural cognition is often a central topic in conversations surrounding cultural linguistics, which in turn plays a key role in the field of cognitive linguistics. Therefore, exploring the study of conceptual metaphors in culture and their impacts on cognition, as well as their influence on culture, holds significant importance. This article aims to provide an overview of cultural cognition and metaphor, and their interplay. It will begin by defining culture and discussing the role of cultural cognition within this framework, before delving into the relationship between conceptual metaphors and cultural cognition, addressing the pertinent questions that arise in this context.